Pozycja samorządu terytorialnego w Konstytucji - Rabska, Teresa (Wydział Prawa i Administracji UAM, 1995)
The strengthening of democratic forms and the deepening of decentralisation processes is a challenging task for the present administration. If these new principles are to harden and stay, however, a reconstruction of the existing administration system must be carried out. On a closer examination of the progress which has been made so far in the work on the new Polish constitution, we are left with an impression that these problems are not yet fully and adequately recognised. What is still missing is a general concept of how the public administration should function and how it should be prepared to realise new tasks which now lie before the State and must be dealt with in a totally new economic environment. A self-governing body of territorial administration constitutes an integral part of public administration. Therefore, its position largely depends on the model ofthat administration. There are two main aspects which play a particularly important role in territorial self-government. They are: the nature of legal subjectivity and the level of decentralisation. Those two 'pillars' of the legal construction require a special explanation. The issue is that the self-government organ must be recognised as a legal entity and assume a legal and public status, whereas the formulas of decentralisation must also absorb the principle of subsidiaries and provide for a level which will be 'the closest ever to the citizen'. These principles are sourced in the European Law and the European Chart of Territorial Self-Government and as such should be obeyed and recognised in administrative structures. These contents should also be reflected in the provisions of the new constitution. What follows from there is a need to expand the self-governing territorial organ and move it to higher levels of administrative division of the state, as well as to extend its participation in the public control function. In this way, a complete system of self-governing organs, operating at different levels would be created. As a result, a need to regulate the interrelations between those organs would arise. Another problem which appears immediately here, is the appointment of a nationwide representation of territorial self-governments. The work which is currently in progress and focused on the drafting of the new constitution of the Republic of Poland offers a real and true chance to define the political system of the whole administration in the country including the self-governing organs. If this chance is missed, there may be a serious delay in the process of system transformations.
Position of a territorial self-government organ in the constitution of the Republic of Poland